Workplace Monitoring in Europe: A Review of Regulatory Perspectives and Developments - Mirosławski, Tomasz (Polish Review of International and European Law, 2026)
The main focus of the article is to examine the evolution of European regulations covering workplace monitoring, focusing on the Council of Europe and European Union frameworks. It analyses how concepts of human rights, understanding of privacy and data protection standards, particularly the ECHR, CFREU, Convention 108+ and GDPR, shape national approaches to the issue of employee surveillance. Emphasis is placed on proportionality, transparency and human dignity as core principles guiding social partners in defining employee privacy in the modern surveillance age. The study highlights that the effectiveness of a current framework depends on coherent national implementation, adaptability to digitalisation and active social dialogues addressing emerging monitoring technologies within workplaces.